Міські голови Одеси на тлі революційних подій 1905 року - Герасименко, В. (Чорноморська минувшина, 2020)
У статті розглянуто питання діяльності очільників міського самоврядування в період реакційних події 1905 року. Одеса пережила три процедури виборів лорд-мера за півроку. Особистості міських голів – П. О. Зеленого, П.А. Крижановського та В.Я. Протопопова – розкриваються через їх рішення, роботу в Думі, інтерв’ю та характеристики з боку преси й сучасників. Виявлені подробиці є необхідними в ракурсі біографічних та просопографічних досліджень міських голів Одеси першої половини ХХ століття. In the beginning of XXth century the imperial, regional, world socio-economic and political processes significantly influenced on the development of Odessa. The unresolved nature of many of the city's internal problems and external influences exacerbated social tensions: the number of antigovernment protests and protests grew, and the labor movement intensified. The article considered the activity of the heads of city self-government during the revolutionary events of 1905. Odessa has gone through three procedures for electing a lord mayor in six months. The activity of personalities of mayors as P. Zelenyi, P. Kryzhanovskyi and V. Protopopov are revealed through their decisions, work in the Duma, interviews and rewievs from the press and contemporaries. P. Zelenyi was a well-known writer with a law education, who took care of charitable societies and educational institutions, participated in the political sphere. His activity as the mayor of Odessa lasted for 8 years (1898-1905). P. Kryzhanovskyi was the lawyer, who connected his life with the judiciary, worked in various cities of the empire. In the «Odessa News» he appeared as a public figure in the city council under the leadership of mayor G.G. Marazli. Kryzhanovskyi's total tenure as mayor was only 13 months (1897, 1905). V. Protopopov was an assistant to the famous lawyer Richter in Odessa, he joined the editorial activities of the Odessa and Elizavetgrad press, for a long time he was the chairman of the jury of the Odesa Judicial Chamber. In December 1905, the devoted lawyer V. Protopopov accepted the exhausted Odessa as a mayor for the next four years (1905-1908). The material for the investigation was singled out from «Odessa News» and «Odessa Listok» newspapers. More that 360 newspapers were analyzed. In the research, the following methods were used: the methods of synthesis and analysis, structural and comparative-historical methods. The revealed details are necessary in the perspective of biographical and prosopographic researches of the Odessa mayors of the first half of the XXth century.